Indicators of children’s social health: development a conceptual framework to assess equity - Abachizadeh, Kambiz; Omidnia, Soheila; Tajlili, Alireza; Masoudifarid, Habibolah (Social Determinants of Health, 2015)
Background: Social health is important to be assessed as a dimension of health. In this study we tried to determine areas and sub-areas of children social health indicators. Methods: In a structured way, we reviewed the main social health databases and documents since 1995, both Iranian and international were reviewed to develop conceptual framework and to extract indicators. Results: According to reviewed documents, indicators of social health were categorized into four groups. In first category indicators are related to system capacities such as facilities and institutions, financial, and human resources. Social system functions are classified as group two. The main subcategories of social health functions are policy development and enforcement, social marketing, community organizing, coalition building and collaboration, education, case management, screening, surveillance, and investigation. In group three, named as social factors, the main determined areas are life skills, early child development, family functioning, and social networks. Indicators related to social outcomes are categorized as group four. The main related positive social outcomes are social wellbeing and happiness and the main negative outcomes are physical health outcome (injuries, infectious diseases, etc.), mental health outcomes, development and learning outcomes, risky behaviors, academic outcomes, and legal outcomes. Conclusion: Our recommended model develops a conceptual framework for child social health indicators. This framework and extracted indicators can be used to compare different populations to assess inequity for evidence based policy making and to implement proper interventions.